2017
DOI: 10.1039/c7nj03168h
|View full text |Cite
|
Sign up to set email alerts
|

A flexible magnesium silicate coated electrospun fiber adsorbent for high-efficiency removal of a toxic cationic herbicide

Abstract: A novel magnesium silicate/PAN composite electrospun fiber adsorbent was prepared and systematically investigated for the removal of the cationic herbicide diquat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…X‐ray photoelectron spectroscopy (XPS) surface survey spectrum of Mg−Si−MTW‐50 confirms the presence of various constituent elements in the framework structure (Figure S2a). The high‐resolution spectrum of Si 2p exhibits a broad peak, which can be deconvoluted into two peaks centred at binding energies of 103.1 eV and 104.0 eV corresponding to Si−O−Mg and Si−O−Si, respectively . Moreover, a distinguish peak centred at 1305.0 eV corresponds to Mg 2+ is present in Si−O−Mg .…”
Section: Resultsmentioning
confidence: 99%
“…X‐ray photoelectron spectroscopy (XPS) surface survey spectrum of Mg−Si−MTW‐50 confirms the presence of various constituent elements in the framework structure (Figure S2a). The high‐resolution spectrum of Si 2p exhibits a broad peak, which can be deconvoluted into two peaks centred at binding energies of 103.1 eV and 104.0 eV corresponding to Si−O−Mg and Si−O−Si, respectively . Moreover, a distinguish peak centred at 1305.0 eV corresponds to Mg 2+ is present in Si−O−Mg .…”
Section: Resultsmentioning
confidence: 99%
“…These peaks suggested that the solid was a mixture of MgO, Mg­(OH) 2 , and magnesium silicate, which is in agreement with the FTIR and XRD as well as TGA data. At the same time, the Si 2p peak of the solid was deconvoluted into two peaks, at 102.10 and 102.36 eV, corresponding to the Si–O and Mg–O–Si bonds of the formed magnesium silicate, respectively . Hydrated MgO–SiO 2 showed a very similar pattern in terms of the Si 2p and Mg 2p peaks with MgO–SiO 2 , suggesting their similar silica removal mechanism.…”
Section: Resultsmentioning
confidence: 87%
“…The removal of dissolved sulfides by adsorption was the object of many works by solutions from different origins: synthetic solutions produced in the laboratory (from sodium sulfide 5 ) and industrial solutions rejected from refinery 12 or tanneries wastewater, 13 with concentrations from 140 μg/l 14 to 1000 mg/l 12 . Various adsorbents have been used for the uptake of sulfides, such as granular ferric hydroxide, 15 porous graphitic carbon/manganese dioxyde, 16 bio‐sorbents, 13 and AC 5,12 . The adsorbents proved efficient removal capacity of sulfides from 29.1 mg/g for granular ferric hydroxide 15 to 500.1 mg/g for graphitic carbon 16 …”
Section: Introductionmentioning
confidence: 99%
“…Various adsorbents have been used for the uptake of sulfides, such as granular ferric hydroxide, 15 porous graphitic carbon/manganese dioxyde, 16 bio‐sorbents, 13 and AC 5,12 . The adsorbents proved efficient removal capacity of sulfides from 29.1 mg/g for granular ferric hydroxide 15 to 500.1 mg/g for graphitic carbon 16 …”
Section: Introductionmentioning
confidence: 99%